2018
DOI: 10.1186/s12969-018-0279-0
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study comparing the childhood arthritis and rheumatology research alliance consensus treatment plans for induction therapy of juvenile proliferative lupus nephritis

Abstract: BackgroundTo reduce treatment variability and facilitate comparative effectiveness studies, the Childhood Arthritis and Rheumatology Research Alliance (CARRA) published consensus treatment plans (CTPs) including one for juvenile proliferative lupus nephritis (LN). Induction immunosuppression CTPs outline treatment with either monthly intravenous (IV) cyclophosphamide (CYC) or mycophenolate mofetil (MMF) in conjunction with one of three corticosteroid (steroid) CTPs: primarily oral, primarily IV or mixed oral/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Since these drugs have a range of well-known side effects, they should only be used for a limited time. There is no consensus on the dosage of glucocorticoids in childhood CLE or on dose reduction [57,58]. However, some studies have shown that a more restrive use of systemic glucocorticoids is not a disadvantage and has fewer side effects [59].…”
Section: Systemic Glucocorticoidsmentioning
confidence: 99%
“…Since these drugs have a range of well-known side effects, they should only be used for a limited time. There is no consensus on the dosage of glucocorticoids in childhood CLE or on dose reduction [57,58]. However, some studies have shown that a more restrive use of systemic glucocorticoids is not a disadvantage and has fewer side effects [59].…”
Section: Systemic Glucocorticoidsmentioning
confidence: 99%
“…Da diese Medikamente eine Reihe von bekannten Nebenwirkungen haben, sollte der Einsatz zeitlich begrenzt sein. Es gibt keinen Konsensus über die Dosierung von Glukokortikoiden bei CLE im Kindesalter beziehungsweise über die Reduktion der Glukokortikoide [57,58]. Es zeigt sich aber in einigen Studien, dass der restriktivere Einsatz von systemischen Glukokortikoiden kein Nachteil ist und weniger Nebenwirkungen hat [59].…”
Section: Mepacrinunclassified
“…Delphi surveys and expert opinion were previously employed to propose standards for CS use (2,3), including for proliferative LN in children as part of the consensus treatment plans for pediatric LN (4). However, when tested in real‐life settings, providers were following the CS dosing recommended by the consensus treatment plans for pediatric LN in only 68% of patients by 3 months of induction therapy for LN and in just 37% of patients by 6 months of induction therapy for LN (5).…”
Section: Introductionmentioning
confidence: 99%